Comparison of 3-month visual outcomes of a new multifocal intraocular lens vs a trifocal intraocular lens. Issue 11 (12th November 2022) - Dick, H. Burkhard; Ang, Robert E.; Corbett, Dean; Hoffmann, Peter; Tetz, Manfred; Villarrubia, Alberto; Palomino, Carlos; Castillo-Gomez, Alfredo; Tsai, Linda; Thomas, Eugenia K.; Janakiraman, Priya
Abstract : TECNIS Synergy multifocal intraocular lens, model ZFR00V, showed improved clinical performance particularly through near distances vs Acrysof PanOptix Trifocal intraocular lens, model TFNT00, in patients undergoing bilateral cataract surgery. Abstract : Purpose: To compare the clinical performance of the TECNIS Synergy multifocal (model ZFR00V) intraocular lens (IOL) with that of the AcrySof PanOptix Trifocal (model TFNT00) IOL in patients undergoing bilateral cataract surgery. Setting: Multicenter clinical setting. Design: Prospective randomized comparative study. Methods: Patients aged 22 years or older were randomly assigned (2:1) to bilateral implantation with ZFR00V or TFNT00 IOLs. End points included the mean binocular distance-corrected near visual acuity (DCNVA) at 40 cm, photopic and mesopic DCNVAs at 33 cm, photopic low-contrast corrected distance visual acuity (CDVA) and mesopic CDVA, nondirected patient responses to an ocular/visual symptoms questionnaire, and safety. Results: Of the 150 patients implanted with IOLs, 95 of the 97 patients with ZFR00V IOLs and 52 of the 53 patients with TFNT00 IOLs completed the 3-month follow-up. Most patients in the ZFR00V and TFNT00 groups achieved 20/25 or better binocular CDVA (100% vs 96.2%) and DCNVA measured at 40 cm (88.4% vs 75.0%) and 33 cm (78.9% vs 51.9%). The mean between-group difference in binocular DCNVA at 40 cm favored ZFR00V IOLs (0.5 lines Snellen; 95% CI, 0.012 to 0.089; P ≤ .05). Similarly, the mean binocular photopic and mesopic DCNVAs at 33 cm (0.8 lines Snellen each; both P ≤ .05 vs TFNT00) and photopic high-contrast and low-contrast CDVA (0.5 lines Snellen each; both P ≤ .05 vs TFNT00) favored ZFR00V IOLs. Patient-reported ocular/visual symptoms and safety were generally similar between the 2 IOLs. Conclusions: The ZFR00V IOL showed an extensive range of vision, particularly through near distances, and better mesopic performance than the TFNT00 IOL in patients undergoing cataract surgery.